Analysis of the Application of Occupational Health and Safety Risk Management at Pt. W Year 2022: Analisis Penerapan Manajemen Risiko Keselamatan Dan Kesehatan Kerja Di Pt. W Tahun 2022 - Dimas Pangestu; Endang Purnawati Rahayu; Welly Sando; Alhidayati Alhidayati; Muhamadiah Muhamadiah (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Risk management is a systematic method of looking at risks and ensuring appropriate action on those risks. It is a means of identifying sources of risks and uncertainties and being able to predict the consequences that will arise and develop the reactions that should be tried to address those risks. This research aims to obtain in -depth information on the analysis of the application of occupational safety and health risk management in PT.W in 2022. This research was conducted using a qualitative research design by conducting in -depth interviews, to 5 people, namely 1 person HSE Super Intendent as the main informant, 1 person supervisor as key informant, and 3 workers as supporting informant . This study was conducted in January-April 2022. The results showed that in the assessment and determination of risk levels were found as many as 20 sources of hazards (hazards) that and cause 22 Accident risks that include 13 risks with low category (Low), 4 risks with category medium (Medium), 5 risks with a high category (High), namely: falling lifting load, overturned lift, hitting workers or other equipment, workers or eqiupment being hit or disturbing other road users, bouncing can injure workers. Recommended to PT.W to pay attention to field activities in each pipe sleeve installation process so that there are no accidents in the field while working.